2009
DOI: 10.1002/j.2334-5837.2009.tb00994.x
|View full text |Cite
|
Sign up to set email alerts
|

6.2.3 Coping with System Evolution ‐ Experiences in Reverse Architecting as a Means to Ease the Evolution of Complex Systems*

Abstract: Creating systems from scratch is time consuming and costly, therefore companies often choose to evolve existing systems. The understanding that a company has about the impact that a change has in the system architecture determines their ability to cope with system evolution.System architects and designers need to have an architecture representation that enables them to understand and to foresee consequences of evolving the system. This representation however is often not documented. Reverse architecting enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
1
0
2
Order By: Relevance
“…Основная проблема методологии снизу-вверх -возможное несоответствие разрабатываемого продукта требованиям. Но при этом, как показано в [1,[7][8][9], требования к продукту неизбежно меняются, причём начинается этот процесс ещё во время разработки. С другой стороны, использование методологии снизу-вверх позволяет быстро получать прототипы системы, которые могут использоваться для постепенной верификации системы на соответствие требованиям, и, что более важно, для уточнения и обновления самих требований.…”
Section: Top-down Vs Bottom-up Methodologies For Adas System Designunclassified
See 1 more Smart Citation
“…Основная проблема методологии снизу-вверх -возможное несоответствие разрабатываемого продукта требованиям. Но при этом, как показано в [1,[7][8][9], требования к продукту неизбежно меняются, причём начинается этот процесс ещё во время разработки. С другой стороны, использование методологии снизу-вверх позволяет быстро получать прототипы системы, которые могут использоваться для постепенной верификации системы на соответствие требованиям, и, что более важно, для уточнения и обновления самих требований.…”
Section: Top-down Vs Bottom-up Methodologies For Adas System Designunclassified
“…Масштабирование и расширение системы в рамках подхода сверху-вниз выражается в формировании обновлённых требований к системе и полной переработке системы по полному циклу проектирования, что подразумевает глобальные изменения в системе, так как подсистемы в концепции методологии сверху-вниз не являются независимыми и тесно связаны с другими компонентами. Изменение характеристик отдельных подсистем, не контролируемое целеполаганием ко всей системе в целом, может оказать непредсказуемое влияние на внутрисистемные взаимодействия и функционирование системы [8,21].…”
Section: композиционный морфизмunclassified
“…A paradigm shift can be observed as the product is not designed in a conventional manner-instead, a family of products is "programmed". Earlier research has found a certain reluctance of the main stakeholder-the designers-to describe products based on UML or SysML [18][19][20]. The designers in this project were younger engineers trained in the engineering framework and were open to this kind of change.…”
Section: Exemplary Application Of the Combined Modelmentioning
confidence: 99%
“…These models and processes include the System Modeling Language (SysML), the Object-Process Methodology (OPM, [11]), Function Analysis Diagrams [12], Computational Functional Basis [13][14][15][16], and the Integrated Function Modeling (IFM) Framework [17]. The application of such models was investigated by several research teams [18][19][20]. In general, these models and processes still remain at an abstract level for the description of the resulting technical system.…”
Section: Introductionmentioning
confidence: 99%
“…Borches PD, Bonnema GM (2009) The approach has been adopted not just for the SDS, but also for capturing knowledge of system aspects that cross system and organizational boundaries.…”
Section: Benefits and Concernsmentioning
confidence: 99%